Ubuntu relational love : decolonizing Black masculinities - Mucina, Devi Dee, 1972- (Winnipeg, Manitoba, Canada : University of Manitoba Press, 2019)
"Ubuntu is a Bantu term meaning humanity. It is also a philosophical and ethical system of thought, from which definitions of humanness, togetherness, and social politics of difference arise. Devi Dee Mucina is a Black Indigenous Ubuntu man. In Ubuntu Relational Love, he uses Ubuntu oratures as tools to address the impacts of Euro-colonialism while regenerating relational Ubuntu governance structures. Called "millet granaries" to reflect the nourishing and sustaining nature of Indigenous knowledges, and written as letters addressed to his mother, father, and children, Mucina's oratures take up questions of geopolitics, social justice, and resistance. Working through personal and historical legacies of dispossession and oppression, he challenges the fragmentation of Indigenous families and cultures and decolonizes impositions of white supremacy and masculinity. Drawing on anti-racist, African feminist, and Ubuntu theories and critically influenced by Indigenous masculinities scholarship in Canada, Ubuntu Relational Love is a powerful and engaging book."--
Includes bibliographical references (pages 209-214) and index.
Issued also in electronic formats.
Keywords: Ubuntu (Philosophy); Kinship; Parenthood; Masculinity; Men, Black; Decolonization; Feminism; Indigenous peoples -- Africa, Southern